The Sensitivity of the Bible Verse Selection Task to the Relationship between Christian Fundamentalism and Religious Outgroup Prejudice - Rouse, Steven V. (Journal of psychology and theology, 2021)
Four different studies provide evidence to support the validity of the Bible Verse Selection Task (BVST) as a measure of the strength of Christian fundamentalist beliefs by showing correlations between BVST scores and measures of negativity toward people who often represent “outgroups” for Christians. That is, respondents who obtained high scores on the BVST (representing a greater tendency to select biblical passages associated with fundamentalism as most central to their faith or belief system) also showed a tendency to obtain high scores on measures of negative feelings, beliefs, behaviors, and attitudes toward atheists, gay men, lesbian women, and Muslims. These relationships were generally consistent across both Christian-only samples and general samples, with statistically significant coefficients obtained for 30 of 32 predicted correlations. These results support the utility of this scale for research purposes.